Physical and Physiological Match-Play Demands and Player Characteristics in Futsal: A Systematic Review - Spyrou, Konstantinos; Freitas, Tomás T.; Marín-Cascales, Elena; Alcaraz, Pedro E. (Frontiers in Psychology, 2020)
Futsal, also known as five-a-side indoor soccer, is a team-sport that is becoming increasingly popular. In fact, the number of futsal-related investigations is growing in recent years. This review aimed to summarize the scientific literature addressing the match-play demands from the following four dimensions: time-motion/external load analysis, physiological, neuromuscular, and biochemical responses to competition. Additionally, it aimed to describe the anthropometric, physiological and neuromuscular characteristics of elite and sub-elite male futsal players, contemplating the differences between competition level. The literature indicates that elite futsal players cover greater total distance, with higher intensities and perform a greater number of sprints during match-play when compared to sub-elite. The physiological demands during competition are high (average intensity of ≥ 85% maximal heart rate and ~80% maximum oxygen uptake [VO2max]), with decrements between the two halves. Research suggests that neuromuscular function decreased and hormonal responses increased up to 24 h after the match. Considering anthropometric characteristics, players present low percentage of body fat, which seems commonplace amongst athletes from different on-court positions and competition levels. Elite players display greater values and at VO2max with respect to sub-elite competitors. Little is known regarding elite and sub-elite futsal players’ neuromuscular abilities (strength, jumping, sprinting and change of direction [COD]). However, it appears that elite players present better sprinting abilities compared to lower level athletes. Futsal players aiming to compete at highest level should focus on developing maximal speed, lower-body power and strength, aerobic capacity and lean muscle mass.